A Comparative Study of the Effects of Interactive Versus Individual Performance Tasks on EFL Learners’ Speaking Skill - رویا خوئی; احسان ذولفقاری یونسی (Journal of Applied Linguistics)
Interaction has always been viewed as a key element in developing the knowledge of an L2 and establishing dynamic communicative episodes. However, it is not always materialized in foreign language learning contexts where access to English speakers is limited. Hence, this study investigated the effects of employing interactive and individual performance tasks on Iranian male EFL learners’ speaking ability. The participants were 32 homogeneous upper-intermediate EFL learners in two intact classes, randomly assigned to two experimental groups. The first experimental group performed problem-solving, reasoning-gap, and opinion-gap tasks individually, and the second group employed problem-solving, reasoning-gap, and information-gap tasks through team-work for 16 sessions. Two speaking pre- and post-tests were administered to evaluate the participants’ oral performance before and after the treatment. The statistical analysis of the data showed no statistically significant difference between the mean scores of the two groups on the speaking post-test, indicating that neither form of performance was superior to the other in the process of developing L2 oral proficiency. However, the results of two paired samples t-tests demonstrated that the learners’ speaking skill had significantly improved in both groups at the end of the experiment. Therefore, the researchers concluded that a careful execution of individual performance tasks in the absence of interaction could also contribute to developing speaking an L2.